Helical water chain mediated proton conductivity in homochiral metal-organic frameworks with unprecedented zeolitic unh-topology - Sahoo, Subash Chandra; Kundu, Tanay; Banerjee, Rahul (Journal of the American Chemical Society, 2011)
Four new homochiral metal-organic framework (MOF) isomers, [Zn(l-L-Cl)(Cl)](H2O)(2) (1), [Zn(l-L-Br)(Br)]-(H2O)(2) (2), [Zn(d-L-Cl)(Cl)(H2O)(2) (3), and [Zn(d-L-Br)-(Br)] (H2O)(2) (4) [L = 3-methyl-2-(pyridin-4-ylmethylamino)-butanoic acid], have been synthesized by using a derivative of L-/D-valine and Zn(CH3COO)(2)center dot 2H(2)O. A three-periodic lattice with a parallel ID helical channel was formed along the crystallographic c-axis. Molecular rearrangement results in an unprecedented zeolitic unh-toparigy in 1-4. In each case, two lattice water molecules (one H-bonded. to halogen atoms) form a secondary helical continuous water chain inside the molecular helix. MOFs 1 and 2 shows different water adsorption properties and hence different water affinity. The arrangement of water molecules inside the channel Was monitored by variable temperature single crystal X-ray diffraction, which indicated that MOF 1 has a higher water holding capacity than MOF 2. In MOF 1, water escapes. at 80 degrees C, while in T the same happens at a much lower temperature (similar to 40 degrees C). All the MOFs reported here shows reversible crystallization by readily reabsorbing moisture. In MOFs 1 and 2, the frameworks are stable after solvent removal, which is confirmed by a single-crystal to single crystal transformation. MOFs 1 and 3 show high proton conductivity of 4.45 x 10(-5) and 4.42 x 10(-5) S cm(-1), respectively, while 2 and 4 shows zero proton conductivity. The above result is attributed to the fact that MOF 1 has a higher water holding capacity than MOF 2.

Structural isomerism and effect of fluorination on gas adsorption in copper-tetrazolate based metal organic frameworks - Pachfule, Pradip; Chen, Yifei; Sahoo, Subash Chandra; Jiang, Jianwen; Banerjee, Rahul (Chemistry of Materials, 2011)
Synthesis, structure, and gas adsorption properties of three Metal Organic Frameworks (MOFs) synthesized from predesigned ligands 4-(1H-tetrazole-5-yl)benzoic acid (4-TBA) and 2-fluoro-4-(1H-tetrazole-5-yl)benzoic acid (2F-4-TBA) along with Cu(II) as an metal precursor has been reported. Among these MOFs, Cu-9(4-TBA)(10)(C2H5OH)(2) (Cu-TBA-1) and Cu-2(4-TBA)(2)(DMF)(C2H5OH) (Cu-TBA-2) are structural isomers. Whereas, Cu-2(4-TBA)(2)(DMF)(C2H5OH) (Cu-TBA-2) and Cu-2(2-F-4-TBA)(2)(DMF)(2) (Cu-TBA-2F) have similar crystal structure. N-2 adsorption isotherms of the activated sample of Cu-TBA-1 and -2 exhibit types-I sorption behavior with a Langmuir and Brunauer-Emmett-Teller (BET) surface area of 686, 402 m(2)/g and 616, 356 m(2)/g, respectively. It is noteworthy that Cu-TBA-1 and -2 adsorbs 1.16 and, 1.54 wt % H-2, while Cu-TBA-2F adsorbs 0.67 wt % at 77 K and 1 atm. On the other hand, Cu-TBA-1 and -2 adsorb 3.08 and 2.54 mmol/g, while Cu-TBA-2F adsorbs 1.27 mmol/g of CO2 at 298 K and 1 bar pressure. H-2 adsorption sites in Cu-TBA-2 and -2F have been analyzed by molecular simulation.
Keywords: CO2 adsorption; fluorination; Hydrogen storage; Metal-organic framework; structural isomerism

Alkali earth metal (Ca, Sr, Ba) based thermostable metal-organic frameworks (MOFs) for proton conduction - Kundu, Tanay; Sahoo, Subash Chandra; Banerjee, Rahul (Chemical Communications, 2012)
{Three new alkaline earth metal based MOFs have been synthesized by using 4,4'-sulfobisbenzoic acid (SBBA) and alkaline earth metal salts M(NO3)(2)

Solid-state thermolysis of anion induced metal-organic frameworks to ZnO microparticles with predefined morphologies: facile synthesis and solar cell studies - Kundu, Tanay; Sahoo, Subash Chandra; Banerjee, Rahul (Crystal Growth & Design, 2012)
Simple one-step solid state thermolysis of two Zn-based homochiral metal organic frameworks (MOFs) leads to a dramatic difference in morphologies which depends on the anion (-Cl and -Br) and calcination environment (air and N-2). Rod-shaped (aspect ratio similar to 20), hexagonal column shaped (aspect ratio similar to 3), and elliptical aggregation of ZnO morphologies (aspect ratio similar to 3) are obtained and characterized. Although these two MOFs possess similar rod-shaped morphology, they produce dramatic change in resulting ZnO microparticle morphologies (from rod-shaped ZnO microparticles in the case of thermolysis of MOP 1 to hexagonal column shaped ZnO microparticles in the case of MOF 2 thermolysis) when calcined in N-2 at 800 degrees C. However, when we calcined both MOF 1 and 2 in air, we encountered similar elliptical aggregation of ZnO microparticles. These ZnO microparticles show permanent porosity, visible light emission centered at 605 or 510 nm. Moreover, they show 0.15% and 0.14% dye sensitized solar cell activity. To the best of our knowledge, this is the first report of dye sensitized solar cell activity of ZnO microparticles obtained from one-step thermolysis of porous homochiral MOFs.

Variable water adsorption in amino acid derivative based homochiral metal organic frameworks - Kundu, Tanay; Sahoo, Subash Chandra; Banerjee, Rahul (Crystal Growth & Design, 2012)
{Six new Cd-containing homochiral metal organic framework materials [

Relating pore hydrophilicity with vapour adsorption capacity in a series of amino acid based metal organic frameworks - Kundu, Tanay; Sahoo, Subash Chandra; Banerjee, Rahul (CrystEngComm, 2013)
A new Zn based porous homochiral metal-organic framework, ThrZnOAc, belonging to unh topology, has been synthesized using pyridyl functionalized threonine and Zn(OAc)(2) as the metal precursor. Stepwise substitution of the homochiral MOF backbone by simply changing the sidearm of the amino acids (isopropyl in the case of valine, methyl in alanine and hydroxyethyl in threonine) resulted in increased water adsorption in ThrZnOAc compared to the previously reported ValZnOAc/AlaZnOAc. Extensive solvent sorption isotherms (water, methanol, isopropanol and toluene) have been carried out, which revealed high solvophilic interaction with polar solvents in ThrZnOAc due to the polar pore [2-hydroxyethyl {-CH(OH)CH3} sidearm of the amino acid], which is not prominent in the corresponding valine/alanine counterparts. The aforementioned functionalization in a series of isostructural amino acid based MOFs with the only difference being in the sidearm and their emergence as enhanced solvophilic materials is unprecedented in the MOF literature.

Salt metathesis in three dimensional metal-organic frameworks (MOFs) with unprecedented hydrolytic regenerability - Kundu, Tanay; Sahoo, Subash Chandra; Saha, Subhadeep; Banerjee, Rahul (Chemical Communications, 2013)
{Eight Zn-based porous (1.2 nm) homochiral MOFs (ValZnX, AlaZnX